2017
DOI: 10.1111/liv.13510
|View full text |Cite
|
Sign up to set email alerts
|

Enoxaparin does not ameliorate liver fibrosis or portal hypertension in rats with advanced cirrhosis

Abstract: Our results do not support a role of enoxaparin for improving liver fibrosis, portal hypertension or endothelial dysfunction in active disease at advanced stages of cirrhosis. These disease-related factors and the possibility of a limited therapeutic window should be considered in future studies evaluating the use of anticoagulants in cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…In particular, the administration of CCl4 by oral gavage requires low quantities of CCl4 and ensures its direct delivery to the liver through the portal vein, diminishing the extrahepatic effects due to the selective accumulation of CCl4 in the liver 20 . The inhalational route is also frequently used 21 , 22 , but it exposes extra-hepatic organs to CCl4 and is more expensive due to the need of large amounts of CCl4 and specific facilities to perform the administration (fume-hoods, filters). Importantly, CCl4 causes liver toxicity in humans and was reasonably anticipated to be a human carcinogen in the 12 th Report on Carcinogens 23 .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the administration of CCl4 by oral gavage requires low quantities of CCl4 and ensures its direct delivery to the liver through the portal vein, diminishing the extrahepatic effects due to the selective accumulation of CCl4 in the liver 20 . The inhalational route is also frequently used 21 , 22 , but it exposes extra-hepatic organs to CCl4 and is more expensive due to the need of large amounts of CCl4 and specific facilities to perform the administration (fume-hoods, filters). Importantly, CCl4 causes liver toxicity in humans and was reasonably anticipated to be a human carcinogen in the 12 th Report on Carcinogens 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Hence, several experimental studies have shown that anticoagulant therapy improves liver fibrosis and reduces portal hypertension [62][63][64][65][66][67][68][69][70][71][72][73], and a clinical trial demonstrated that anticoagulation led to a reduction in portal thrombosis and other complications of liver disease and to increase in survival [74]. New clinical trials are needed in order to confirm these preliminary results and to establish whether the stage of liver disease may influence its efficacy [75].…”
Section: Pathophysiologymentioning
confidence: 99%
“…36,37 There are conflicting data on the effects of LMWH and DOACs on portal hypertension in cirrhosis rat models. [38][39][40] One group has demonstrated that both enoxaparin and rivaroxaban decreased portal hypertension and fibrosis in the rat cirrhosis model. It was hypothesized that these effects are mediated through deactivation of HSCs, as desmin and α-smooth muscle actin were both decreased in the rats treated with a factor Xa inhibitor.…”
Section: Mechanism Of Thrombosis and Role Of Doacs As Antifibrotic Agmentioning
confidence: 99%
“…40 However, another study demonstrated no improvements in portal hypertension in cirrhotic rats treated with enoxaparin. 39 Like thrombin, inhibition of factor Xa has also been linked to decreased fibrosis formation in the skin, but at the cost of decreased wound healing. 41 While most factors in the coagulation cascade are reduced in end-stage liver disease, von Willebrand factor (VWF) is increased.…”
Section: Mechanism Of Thrombosis and Role Of Doacs As Antifibrotic Agmentioning
confidence: 99%